2014
DOI: 10.1002/pola.27170
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated brush growth on nanoparticle surfaces by reversible addition‐fragmentation chain transfer polymerization

Abstract: It is now well established that controlling the grafted chain lengths and densities on nanoparticle surfaces determines the effective interactions between particles, and their assembly. Here, we present unusual kinetic results for achieving grafted chain lengths longer than the free chains using reversible addition‐fragmentation chain transfer (RAFT) polymerization and discuss the limitations to obtaining polymer grafting density higher than ∼0.06 chains/nm2. We observe that surface initiated polymerization gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…A comparison of the SEC data of degrafted and free PHMA polymers (Figures 2b and S10b, Table 1) shows that the molecular weight of the free polymers is lower than tethered polymer chains. Other authors have also reported longer chains for the grafts than for free polymers, 39,42 and as above mentioned the effect appears to be a consequence of the reduced mobility of the tethered propagating chains, which in turn limits chain termination. The slight broadening of the molecular weight distributions observed for the PMMA synthesized via surface-initiated polymerization is in good agreement with the behavior predicted by Turgman-Cohen and Genzer, i.e.…”
Section: Resultsmentioning
confidence: 66%
“…A comparison of the SEC data of degrafted and free PHMA polymers (Figures 2b and S10b, Table 1) shows that the molecular weight of the free polymers is lower than tethered polymer chains. Other authors have also reported longer chains for the grafts than for free polymers, 39,42 and as above mentioned the effect appears to be a consequence of the reduced mobility of the tethered propagating chains, which in turn limits chain termination. The slight broadening of the molecular weight distributions observed for the PMMA synthesized via surface-initiated polymerization is in good agreement with the behavior predicted by Turgman-Cohen and Genzer, i.e.…”
Section: Resultsmentioning
confidence: 66%
“…PGNs with canopy dominated by SDPB conformations ( r c ⩽ r 0 ) were synthesized via surface-initiated reversible addition–fragmentation chain transfer (RAFT) polymerization of polystyrene (PS) from iron oxide nanoparticles ( r 0 = 3.85 ± 0.55 nm) . In brief, iron oxide nanoparticles were first synthesized and stabilized with oleic acid and oleylamine.…”
Section: Resultsmentioning
confidence: 99%
“…Oleic acid and oleylamine-stabilized Fe 3 O 4 nanoparticles were synthesized by the high-temperature thermal decomposition method . Fe 3 O 4 –PS PGNs were synthesized by surface-initiated reversible addition–fragmentation chain transfer (RAFT) polymerization based on previously published protocols with the same materials used . To remove free chains, the product was washed multiple times by suspending in toluene followed by pelletization.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Jiao et al [ 96 ] demonstrated the importance of CTA coverage on the kinetics of RAFT polymerization. In this study, the polymerization of styrene with CTA-functionalized Fe 3 O 4 NPs in the presence of free CTAs was performed.…”
Section: Core-brush Nanoparticlesmentioning
confidence: 99%